Return to paradise [Season 1] [videorecording (DVD)] - Hall, James (Screenwriter); Mattessi, Peter; Thorogood, Robert (BBC Studios, 2025)
"DI Mackenzie Clarke is the toast of London's Metropolitan Police, renowned for solving impossible murders with inspired detective work. When she's accused of tampering with evidence, her career is in tatters, and she has no choice but to return home. She's still no fan of the idyllic beachside town of Dolphin Cove and, frankly, no one there really likes Mackenzie either. But when a murder case shocks the Dolphin Cove Surf Life Saving Carnival, Mackenzie can't help getting involved. Can she crack the case and confront her past along the way?"--